2013
DOI: 10.1177/193758671300700104
|View full text |Cite
|
Sign up to set email alerts
|

When the World Is Closing In: Effects of Perceived Room Brightness and Communicated Threat During Patient-Physician Interaction

Abstract: Lighting, patients, physicians, satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…These combined findings suggest that when the aim is to stimulate social interactions amongst people who are socially withdrawn (i.e., alone) or hesitant to engage in social interaction, spacious nature scenes might be particularly effective. These findings corroborate previous research showing that spacious (indoor) environments stimulate interpersonal communication (i.e., self-disclosure- [52,53]). Additionally, it is worth mentioning that the difference between spacious and dense scenes was particularly prominent when the dense scene appeared after the spacious scene, hinting at the importance of order of appearance and related contrast effects.…”
Section: Discussionsupporting
confidence: 91%
“…These combined findings suggest that when the aim is to stimulate social interactions amongst people who are socially withdrawn (i.e., alone) or hesitant to engage in social interaction, spacious nature scenes might be particularly effective. These findings corroborate previous research showing that spacious (indoor) environments stimulate interpersonal communication (i.e., self-disclosure- [52,53]). Additionally, it is worth mentioning that the difference between spacious and dense scenes was particularly prominent when the dense scene appeared after the spacious scene, hinting at the importance of order of appearance and related contrast effects.…”
Section: Discussionsupporting
confidence: 91%
“…Further, Gifford (1988) found that more intimate communication takes place in bright compared to dim lighting conditions. In yet another study ( Okken et al, 2013 ) investigating the level of disclosure between patient and physician, it was found that in situations of high perceived threat (to health), brightly lit consulting rooms elicited greater positive affective experiences and greater intended self-disclosure due to an increase in perceived spaciousness caused by brightness of light.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that simple manipulations increasing merely the perceived spaciousness may positively affect the interview. In this study, we looked at room size and seating distances, yet there are other aspects – related to architecture and interior design – that influence interviewee’s perceptions of spaciousness which remain to be tested within an investigative interview context, for example, lighting (Gifford, ; Okken, Rompay, & Pruyn, a, b) as well as the room’s colour (Oberfeld, Hecht & Gamer, ) and ceiling height (Meyers‐Levy & Zhu, ).…”
Section: Discussionmentioning
confidence: 99%